SSP silicone-, lipid- and SPMD-water partition coefficients of seventy hydrophobic organic contaminants and evaluation of the water concentration calculator for SPMD - Smedes, Foppe (Chemosphere, 2019)
Passive sampling is increasingly applied for monitoring neutral hydrophobic compounds (HOC) in various environmental media like water, sediment, air and also soft biota tissue. Passive samplers for HOC are often constructed from permeable polymers like silicone and polyethylene (PE), while also SPMD are often applied. Their HOC uptake can be converted to freely dissolved or equivalent lipid-based concentrations using appropriate partition coefficients with or without the use of kinetic uptake models to adjust for non-equilibrium. To facilitate such conversions for seventy HOC partition coefficients are derived by combining polymer-water for Altesil™ silicone and PE, with new and earlier published polymer-polymer, polymer-lipid partition coefficients. Derived SSP silicone-water, lipid-water (Klip/w), and SPMD-water (Kspmd/w) partition coefficients demonstrate good agreement with literature data, except for Kspmd/w. For SPMD, this work demonstrates a linear Kspmd/w - Kow relationship (R2 = 0.99) in contrast to the parabolic Kspmd/w - Kow relationship utilized in the USGS "SPMD Water Concentrations Calculator". Following a thorough evaluation of this Calculator it is recommended that in combination with revised Kspmd/w, a radical different model approach should be used for obtaining accurate water concentrations from passive sampling with SPMD.
Keywords: Partition coefficient; polycyklické aromatické uhlovodíky; Silicones; Lipid; Hydrophobic and Hydrophilic Interactions; Environmental Monitoring; lipidy; Polyethylene; Polycyclic Aromatic Hydrocarbons; polymery; Hydrophobic organic compounds; monitorování životního prostředí; Polymers; polyethylen; voda; Lipids; Water Pollutants, Chemical; Freely dissolved; Semi-permeable membrane device; Water; Passive sampling; hydrofobní a hydrofilní interakce; chemické látky znečišťující vodu; silikony